2016
DOI: 10.1097/pcc.0000000000000709
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Hypertension and Cerebral Hypoperfusion in Children With Severe Traumatic Brain Injury: Thresholds and Burden in Accidental and Abusive Insults

Abstract: Objective The evidence to guide therapy in pediatric TBI is lacking, including insight into the ICP/CPP thresholds in abusive head trauma (AHT). We examined ICP/CPP thresholds and indices of ICP and CPP burden in relationship to outcome in severe TBI and in accidental and AHT cohorts. Design A prospective observational study. Setting PICU in a tertiary children’s hospital. Patients Children <18y admitted to PICU with severe TBI and had ICP monitoring. Measurements and Main Results A pediatric TBI datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 26 publications
(37 reference statements)
2
13
0
2
Order By: Relevance
“…This is a novel and potentially important finding particularly given the well-known paucity of ICP monitoring in young children (some presumed to have AHT) reported by Bennett and colleagues (44). Our finding certainly suggests that victims of AHT have increased ICP and could likely benefit from ICP monitoring and ICP-directed therapy as others have suggested (45). …”
Section: Discussionsupporting
confidence: 71%
“…This is a novel and potentially important finding particularly given the well-known paucity of ICP monitoring in young children (some presumed to have AHT) reported by Bennett and colleagues (44). Our finding certainly suggests that victims of AHT have increased ICP and could likely benefit from ICP monitoring and ICP-directed therapy as others have suggested (45). …”
Section: Discussionsupporting
confidence: 71%
“…Treatment threshold for ICP in the pediatric patient is based on 12 retrospective and prospective studies examining target values for lowering ICP to improve clinical outcome (10). Most studies applied an ICP threshold of 20 mmHg and reported lower ICP values in patients with a favorable outcome compared to those with an unfavorable outcome (64)(65)(66)(67)(68)(69)(70). Few studies examined if different threshold values resulted in different outcome [respectively 14/20/30 mmHg (69) and 15/20 mmHg (71)].…”
Section: The Threshold For Treatment Of Intracranial Hypertensionmentioning
confidence: 99%
“…In a study evaluating adherence to the 2003 Pediatric TBI guidelines in children with severe TBI who survived past 48 hours of admission, for every 1% increase in adherence there was a 1% decrease in the chance of a poor outcome at discharge (42). Multiple predictors of unfavorable neurologic outcome following pediatric TBI have been described, including elevated intracranial pressure and decreased cerebral perfusion pressures (37,42,101), low Glasgow Coma Scale (GCS) on admission (40,41,44,46), subarachnoid hemorrhage and abnormal basal cisterns (35,44), and cerebral edema (35,41,46) on neuroimaging. However, several randomized controlled trials in pediatric TBI investigating therapies such as hypothermia (102), decompressive craniectomy (103), or immune-enhancing diet (104), have failed to improve patient outcomes.…”
Section: Neurologic Outcomes Following Picu Carementioning
confidence: 99%